2015
DOI: 10.1021/acs.energyfuels.5b01716
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Soot Formed during the Pyrolysis of Athabasca Oil Sand Asphaltenes

Abstract: Asphaltenes are formed during the primary upgrading process of bitumen. Gasification is considered as a good option for conversion of the low-value asphaltenes into syngas. Syngas can later be used in the generation of steam for steam-assisted gravity drainage, and the hydrogen from the syngas can be used for upgrading. Understanding the decomposition of asphaltenes, the subsequent formation of soot, and the properties of soot enables optimization of the process of asphaltene gasification. In this work, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This absence may be due to either the large quantity of amorphous carbon present in the sample or the V and Ni present as organometallic form in the soot. The TEM analysis of the pyrolysis soot, as shown in Vinoj et al, also could not detect V or Ni in the soot collected from the pyrolysis experiment.…”
Section: Results and Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…This absence may be due to either the large quantity of amorphous carbon present in the sample or the V and Ni present as organometallic form in the soot. The TEM analysis of the pyrolysis soot, as shown in Vinoj et al, also could not detect V or Ni in the soot collected from the pyrolysis experiment.…”
Section: Results and Discussionmentioning
confidence: 92%
“…Of the 13 stages available, it is possible that fine char particles and ash particles will enter the cascade impactor. The morphology of the soot particles collected are examined using scanning electron microscopy (SEM), and it is confirmed that the contamination is limited to the top few stages of the impactor . This may include one or two top stages or sometimes a maximum of five stages.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations